1
8(2 + t) - 5(t - 1)

do you guys know the answer i need help you guy

2 Answer

2
U multiply the 8 into the brackets, same with the 5 to get 16+8t - 5t -5, now you can isolate the t, 11+3t, divide it all by 3, to get 11/3+t, now move the 11/3 to the other side of the = to get, -11/3=t
Edit
avatar
Moriah Shields
15.5k 3 10 26
answered 6 months ago
2

Answer:

21 + 3t

Step-by-step explanation:

Use distributive property: a*(b +c) =(a*b) + (a*c)

8(2 +t) - 5(t - 1) = 2*8 + t *8 + t *(-5) - 1*(-5)

                       = 16 + 8t -5t + 5

                       = 16 + 5 + 8t - 5t   {Combine like terms}

                       = 21 + 3t

Edit
avatar
Ms. Vida Weissnat
15.5k 3 10 26
answered 6 months ago